Radijska igra - Gruden, Lučka (Slavistična revija, 2017)
This article is based on audio samples of good practice in radio plays. The samples were selected to emphasize features essential to radio and its most structured genre (i.e., the radio play or so-called sound theatre). They are: the illusion of intimate contact, the illusion of simultaneity, the paraverbal as the strongest signal in a spoken message, the hierarchy of voices, identifying the listener and director as "primary listener," minimalism, segmented composition that can catch even the casual listener, recycling, and silence as a powerful compositional and expressive elThis article is based on audio samples of good practice in radio plays. The samples were selected to emphasize features essential to radio and its most structured genre (i.e., the radio play or so-called sound theatre). They are: the illusion of intimate contact, the illusion of simultaneity, the paraverbal as the strongest signal in a spoken message, the hierarchy of voices, identifying the listener and director as "primary listener," minimalism, segmented composition that can catch even the casual listener, recycling, and silence as a powerful compositional and expressive element.ement.
Keywords: beseda; gledališče; intermediality; literature; medmedialnost; paraverbal; paraverbalno; production; produkcija; radijska igra; radio; radio play; Slovene literature; slovenska književnost; sound; theater; theatre; zvok